2012
DOI: 10.1097/jnr.0b013e3182748f26
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Women Who Have Experienced Intrauterine Insemination

Abstract: The factors studied are important to understand psychological distress in women who have undergone IUI treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The average BSRS‐5 score was 4·01 (SD = 3·63) for OPU; but it was 5·0 (SD = 4·1) for IUI and 7·48 (SD = 4·50) for IVF–ET (Lin et al . ). According to the cut‐off point of a BSRS‐5 score, 32·5%, 29·0% and 61·0% of women undergoing IUI, OPU and IVF–ET, respectively, were suffering from psychological distress (Lin et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The average BSRS‐5 score was 4·01 (SD = 3·63) for OPU; but it was 5·0 (SD = 4·1) for IUI and 7·48 (SD = 4·50) for IVF–ET (Lin et al . ). According to the cut‐off point of a BSRS‐5 score, 32·5%, 29·0% and 61·0% of women undergoing IUI, OPU and IVF–ET, respectively, were suffering from psychological distress (Lin et al .…”
Section: Discussionmentioning
confidence: 97%
“…According to the cut‐off point of a BSRS‐5 score, 32·5%, 29·0% and 61·0% of women undergoing IUI, OPU and IVF–ET, respectively, were suffering from psychological distress (Lin et al . ). The percentage was higher than ordinary females, which is 23·1% (Tsou ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These participants were undergoing intrauterine insemination, which Lin et al found to be psychologically distressing to some women. The final strength of the study was the inclusion of both partners because infertility is a shared experience [3]. The importance here is that we can compare and contrast the differences between experiences.…”
Section: To the Editormentioning
confidence: 99%